Politics of Settlement and Sustainable Democracy in Nigeria: Study of Abia State (1999 -2019) - Ifegwu, A. Nduka; Okere, J. O. (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Settlement politics, the proceeds of politics of godfatherism have been identified as one of the social phenomenon that rapes democracy and what it stands for in Nigeria. The article focuses on politics of settlement and sustainable democracy in Nigeria: study of Abia state (1999-2019).It aimed at finding the factors that aids politics of settlement and its effect on the society. The study employed the descriptive approach therefore; data were collected from secondary sources. The theoretical framework is based on the theory of Reciprocity and prebendalism. It was observed that systemic institutional failure, porous constitutional and legal framework, apathetic populace, power of incumbency, among others are factors that facilitate the menace of settlement politics. The study also show that its effect are: electoral malpractices, treasury looting and its attendant underdevelopment, insecurity and poor governance etc. The study therefore explains the dominant pattern of settlement of politics; and recommends the revamping of the public institutions as well as strengthens the legal framework for participatory democracy. Political mass education, popular participation in governance as means to ameliorate this societal evil and sustain the democratic structure.